Fabiola Escobar: capstone - Escobar, Fabiola, artist (Colorado State University. Libraries, 2026)
Artist's statement: Design is rarely about the object itself; it is about the space between the viewer and the visual—the immediate, visceral spark of recognition. My practice is rooted in the intersection of graphic design, cultural storytelling, and intentional communication. With a background in Media Communications and Art History, I approach design as both a visual and conceptual language—one that possesses the unique power to preserve identity, evoke latent emotion, and bridge communities across time and place. My work is driven by a fascination with how color, form, and composition dictate human perception. I am drawn to earthy, organic visual systems that reflect themes of belonging, memory, and the environment. In a world of fleeting digital interactions, I aim to create experiences that feel grounded and alive—where technical clarity meets emotional resonance. I believe that every choice in the design process is a narrative decision. Whether through the grain of a texture or the weight of a typeface, my goal is to translate abstract feelings into tangible forms. I thrive in collaborative environments where design is used as a tool for growth and connection, drawing on my experience in branding and social strategy to communicate with purpose. Ultimately, I strive to contribute design that does more than capture attention—it carries intention, weaving personal identity into collective narratives through the deliberate harmony of color, emotion, and form.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design